Fabrication of polymer-based self-assembly nanocarriers loaded with a crizotinib and gemcitabine: potential therapeutics for the treatment of endometrial cancer. Issue 1 (2nd January 2022) - Yang, Jiaolin; Guo, Hongrui; Lei, Jing; Zhang, Sanyuan; Zhang, Shaoguo; Bai, Jirong; Li, Sufen
Abstract: Combination therapy in cancer therapy has been widely used for its positive attributes, such as minimizing the undesirable side effects of chemotherapies and enhancing the therapeutic effects on different cancers. Compared with free drugs crizotinib (CRZ) and gemcitabine (GEM), CRZ@GEM-NPs could remarkably improve the cytotoxicity for endometrial cancer (EC) cells (Ishikawa cells and KLE cells) after treatment with MTT assay. In this study, CRZ and GEM were conjugated to tri-block copolymer poly(ε-caprolactone)-poly(ethylene glycol)-poly(ε-caprolactone) (PCL-PEG-PCL, known as NPs). The fabricated nanoparticles were characterized by the high-resolution transmission electron microscopy (HR-TEM), and the particles size and zeta potential were investigated by the dynamic light scattering analysis. Further, the morphological features of the EC cell lines were examined by the biochemical staining assays. Morphological changes in endometrial cells morphology revealed by nuclear fragmentation and nuclear condensation (the hallmarks of apoptosis) were noted upon treatment with CRZ@GEM-NPs to the Ishikawa and KLE cancer cells. In addition, resulting in the highest ratio of apoptosis and mitochondrial membrane potential shows the cell death through the mitochondrial membrane potential. In vivo, systemic toxicity studies showed no histological changes and substantial blood biochemical with the near-normal appearance of the organs upon treatment with CRZ@GEM-NPs. Overall, the targeted combination suitable therapeutic framework may be a promising candidate for improved EC therapy.